Microbiota-Gut-Brain Axis and Mental Health - Bertolín-Guillén, José Manuel (British Journal of Healthcare and Medical Research, 2024)
Intestinal microbes seem to be direct mediators in psychopathology, although the exact relationship between microbiome/microbiota and psychism is unknown. This brief structured bibliographic review is quick secondary research conducted with the aim of synthetically compiling the clinically relevant information on this topic, taking into account that the qualified primary research published is limited, complex and heterogeneous. Non systematic search in several well qualified international academic bibliographic indexes obtaining n=80 references. Results revealed that host microbiota have multiple psycho-neuro-gastro-enterological implications via neuroendocrine, nervous and immune pathways. Microbiota also entail an essential impact on hippocampus-dependent learning and memory. Next, the relevant integration of genomics and metabolomics is highlighted so as to explain its possible causal effects on anxiety, depressive and other disorders, as well as the bidirectional implication of the entire vagus nerve in depression through the microbiota-gut-brain axis. Lastly, the possible favourable effects of interventions on such axis in order to improve mental health are mentioned. On the other hand, psychotropic drugs are increasingly used to treat functional gastrointestinal disorders. In conclusions, to modulate intestinal microbiota is a promising and useful therapeutic strategy for various mental, behavioural and neurodevelopmental disorders. It is important to coordinate relevant complementary medical care specialisations in this regard.